On Gerridae (Insecta: Heteroptera) from Bhutan, with description of a new species of Onychotrechus Kirkaldy, 1903 - Zettel, Herbert; Duc, Tran Anh (Zootaxa, 2007)
Hitherto the water striders (Gerridae) of Bhutan have been almost unknown. Only one species, Metrocoris compar (Buchanan-White, 1883), has been reported. Mainly based on new collections, the present study raises the number of known species to nine. Onychotrechus jaechi sp.n. is described; it is closely related to O. robustus Andersen, 1980 described from northwestern India.